Kesejahteraan Subjektif Otaku: Analisis Identitas Sosial, Keterlibatan Komunitas, dan Penilaian Ulang Kognitif - Purwandari, Eny; Rista Nur Hamidah (Mediapsi, 2025)
This study aims to explore the role of cognitive reappraisal as a mediator between social identity and community involvement with subjective well-being among otaku. Otaku, known for their deep interest in Japanese pop culture such as anime and manga, often face challenges related to psychological well-being. Based on social identity theory and emotion regulation, this study examines how social identity and involvement in the otaku community can enhance subjective well-being through cognitive reappraisal. Using SEM-PLS analysis, this study involved 377 participants identified as otaku. The results indicate that social identity and community involvement are positively and significantly related to cognitive reappraisal, which, in turn, is closely related to subjective well-being. These findings highlight the importance of cognitive reappraisal as a mediator in improving the subjective well-being of otaku. The implications of these findings provide insights for practitioners to design more effective interventions to enhance the psychological well-being of otaku.